FRI0006 PROTECTIVE ROLE OF THE PROPROTEIN CONVERTASE SUBTILISIN/KEXIN TYPE 9 (PCSK9) RS2495477 POLYMORPHISM IN PATIENTS WITH RHEUMATOID ARTHRITIS AND SUBCLINICAL ATHEROSCLEROSIS. (June 2019) - Remuzgo-Martínez, Sara; Genre, Fernanda; Pulito-Cueto, Verónica; Corrales, Alfonso; Llorca, Javier; Mijares, Verónica; Lera-Gómez, Leticia; Portilla, Virginia; Ferraz-Amaro, Iván; Castañeda, Santos; Gualillo, Oreste; Ibanez, Javier Martin; et al.
Abstract : Background: RA is associated with the development of cardiovascular (CV) disease and subclinical atherosclerosis 1 . The presence of carotid plaques assessed by ultrasonography studies is a surrogate marker for subclinical atherosclerosis 2 . Proprotein convertase subtilisin/kexin type 9 (PCSK9) is involved in homeostasis of cholesterol, a traditional CV risk factor related to RA and atherosclerosis 1, 3 . PCSK9 polymorphisms can both increase and decrease the risk of CV disease in patients with atherosclerosis 3 . Moreover, PCSK9 levels have been also related with CV risk 4 . However, there is little information on PCSK9 in RA. Objectives: To assess the role of several PCSK9 polymorphisms in RA and subclinical atherosclerosis in RA as well as to determine if these ones may influence on PCSK9 mRNA and protein levels. Methods: PCSK9 rs2479409, rs11583680, rs2483205, rs2495477 and rs562556 polymorphisms were genotyped in 1, 169 Spanish RA patients, who met the 1987 ACR and the 2010 ACR/EULAR criteria for RA 5-6, and 528 healthy controls. Associations were estimated using odds ratios (OR) and 95% confidence intervals (CI). The potential association between PCSK9 polymorphisms in both RA and controls and the presence/absence of carotid plaques in RA was evaluated by logistic regression. PCSK9 mRNA expression and PCSK9 serum levels were determined by qPCR and ELISA, respectively. All results were adjusted by sex, age and traditional CV risk factors. Results: Significant differences in the allele frequencies of PCSK9 rs2495477 between RA patients and controls were found (minor allele: OR=0.55, 95% CI=0.34-0.89, p=0.01). A significant association between minor allele of rs2495477 and carotid plaques was also disclosed in RA patients (OR=0.72, 95% CI=0.56-0.92, p=0.01). PCSK9 levels were significantly decreased in RA patients carrying rs2495477 minor allele compared to controls (97.8 ± 104.9 vs 235.8 ± 93.5 ng/mL, p=0.001). None of the five PCSK9 polymorphisms influenced on its expression. Conclusion: Our study showed for the first time that PCSK9 rs2495477 confers protection against RA susceptibility and the development of subclinical atherosclerosis in RA patients. Furthermore, rs2495477 decreased PCSK9 serum levels in RA that may be crucial to control the disease. References: [1] Autoimmun Rev. 2016; 15: 1013–30. [2] Ann Rheum Dis. 2014; 73: 722–7. [3] J Am Coll Cardiol. 2005; 45: 1611–9. [4] Atherosclerosis. 2016; 252: 50–60. [5] Arthritis Rheum. 1988; 31: 315–24. [6] Arthritis Rheum. 2010; 62: 2569–81. Acknowledgement: Study supported by ERDF and PI15/00525 (ISCIII).Personal funds, SR-M: RD16/0012/0009 (ISCIII-ERDF); FG: Sara Borrell fellowship CD15/00095 (ISCIII-ESF); VP-C: PREVAL18/01 (IDIVAL); VM and RL-M: Miguel Servet type I CP16/00033 (ISCIII-ERDF, ISCIII-ESF). Disclosure of Interests: Sara Remuzgo-Martínez: None declared, Fernanda Genre: None declared, Verónica Pulito-Cueto: None declared, Alfonso Corrales: None declared, Javier Llorca: None declared, Verónica Mijares: None declared, Leticia Lera-Gómez: None declared, Virginia Portilla: None declared, Iván Ferraz-Amaro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Oreste Gualillo: None declared, Javier Martin Ibanez: None declared, Ricardo Blanco: None declared, Raquel López-Mejías: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi.